A intersetorialidade no processo de construção da política de saúde brasileira - Abreu, Cassiane Cominoti (2009)
This study aims at analyzing how the intersectoriality was inserted in the construction process of the Brazilian health policy, having the debate built by the movement and by the sanitary reform and the National Plenary Health as its basis in the 70 s and 80 s, and identifying the intersectoriality in the debate of international health conferences of the World Health Organization. The research is characterized by being qualitative, oriented by the materialistic-historical-dialectic method. A documental and field research was used. The first one involved the collection and analysis of documents which were formulated in the studied periodicity and the field research was performed in four interviews with participants of the national plenary health. The content analysis was used for the data analysis. The study indicates that in the construction process of the Brazilian health policy there were two societary projects in dispute that congregated different meanings from intersectoriality. The neoliberal project defends a meaning of intersectoriality based on the articulation among sectors in a technical and rational perspective which hinders a political and ideological meaning in favor of the reduction of financial resources for the health policy. This is the meaning for intersectoriality present in the international conferences of WHO and it had a strong influence in the 7th National Health Conference in Brazil. The project defended by the sanitary reform kept a meaning of intersectoriality in favor of the articulation among social policies and the expansion of social rights with the consequent consolidation of health concept defended by the sanitary movement. The study concludes that intersectoriality can be paradoxically restrictive and reasserting of collective projects structured around the overcoming of inequality and social inequity conditions.